Integrated nutrient management as a strategy for higher production of pearl millet and wheat under saline water irrigation on sandy loam soils of Haryana - Asha, V; Parmod, K Y; Rajpaul, Y; Ankush, K; Khatera, Q; Charan, S; Ram, P (Plant Science Today, 2026)
The poor quality irrigation water is a major cause of the development of soil salinity and reduced agricultural production in the arid and semiarid areas. Although pearl millet and wheat are moderately salinity-tolerant crops, their productivity is affected by salinity to a large extent. A field experiment was conducted to evaluate the effect of integrated nutrient management on yield and yield attributes of pearl millet and wheat under saline water irrigation during 2022-23 and 2023-24. The experiment consisted of twelve treatments, viz. T1 [(75 % recommended dose of fertilizers (RDF)], T2 (100 % RDF), T3 [75 % RDF + ST-3 (Azotobacter chroococcum)], T4 (100 % RDF + ST-3), T5 [75 % RDF + 2.5 t ha-1 biogas slurry (BGS) + ST-3], T6 (100 % RDF + 2.5 t ha-1 BGS + ST-3), T7 [75 % RDF + 2.5 t ha-1 vermicompost (VC) + ST-3], T8 (100 % RDF + 2.5 t ha-1 VC + ST-3), T9 [75 % RDF + 10 t ha-1 farm yard manure (FYM) + biomix], T10 (100 % RDF + 10 t ha-1 FYM + biomix), T11 (75 % RDF + 2.5 t ha-1 VC + biomix) and T12 (100 % RDF + 2.5 t ha-1 VC + biomix). Results revealed that the number of effective tillers per meter row length, earhead/spike length and the plant height increased with integrated nutrient management and maximum values of these parameters were observed under T10. However, these parameters decreased under the sole application of inorganic fertilisers under saline water irrigation in both pearl millet and wheat crops. The highest grain and stover yield, viz. 27.43 and 78.19 q ha-1 of pearl millet; grain and straw yield of wheat, viz. 38.66 and 55.18 q ha-1 was also reported under treatment T10.